Analisis Tuturan Direktif dan Nilai Budaya pada Buku Al’arabiyah Bayna Yadayka - Tatang Tatang; Syihabuddin Syihabuddin (UIN Maulana Malik Ibrahim Malang, 2014)
This article examines the types of directive speech act in the book Al’arabiyah Bayna Yadayka, and its values of Arabic culture. This study was motivated by the lack of students’ understanding of Arabic culture, whereas they are prospecting to be Arabic teachers. To examine this issue we used a descriptive method with critical discourse analysis, comparative analysis, and pragmatic analysis which is based on Grice’s and Leech’s theories. The data analysis found that in the Al’Arabiyyah Yadayka Baina there are 93 types of questions using directive speech, 8 of solicitation, 9 of petition, 9 of offers, 2 of rejection, and 1 of prohibition. The directive speech contains the traditions and values of Arab and Islamic cultures, i.e the Arabic speech system which is directive, assertive, and straightforward, the use of insya Allah phrase, the holiday traditions, the worships, the tradition of similar speech opponents, the factual topics, and the topics in the Islamic laws. This tradition constitutes the principle of cooperation and politeness. This Arabic communication and the Islamic values must be taught to the Arabic students to improve their multicultural competence and the Islamic values. Artikel ini menelaah jenis tindak tutur direktif yang terdapat dalam buku Al’arabiyah Bayna Yadayka, serta nilai kebudayaan yang terkandung di dalamnya. Telaah ini dilatarbelakangi oleh rendahnya pemahaman budaya mahasiswa akan nilai budaya Arab, padahal mereka merupakan calon guru bahasa Arab. Untuk menelaah persoalan ini digunakan metode deskriptif dengan teknik analisis wacana kritis, analisis komparatif, dan analisis pragmatik yang didasarkan pada teori Grice dan Leech. Dari analisis data disimpulkan bahwa dalam buku Al ‘Arabiyyah Baina Yadayka terdapat jenis tuturan direktif pertanyaan 93 buah, ajakan 8 buah, permohonan 9 buah, penawaran 9 buah, penolakan 2 buah, dan larangan 1 buah. Di dalam tuturan direktif terkandung tradisi dan nilai-nilai budaya Arab dan Islam, yaitu cara bertutur orang Arab yang langsung, tegas, dan lugas, penggunaan ungkapan insya Allah, tradisi hari raya, peribadatan, tradisi lawan tutur yang sejenis, topik yang faktual, dan topik yang sejalan dengan syariat. Tradisi ini memenuhi prinsip kerjasama dan kesantunan berbahasa. Cara berkomunikasi orang Arab seperti ini serta nilai keislaman yang terkandung di dalamnya perlu diajarkan kepada pembelajar bahasa Arab agar mereka memiliki kompetensi multikultural dan nilai-nilai keislaman.